Palaeocurrent directions as an indicator of Pindos foreland evolution (central and southern part), Western Greece - VAKALAS, J.; ANANIADIS, G.; MPOURLOKAS, J.; POULIMENOS, D.; GETSOS, K.; PANTOPOULOS, G.; AVRAMIDIS, P.; ZELILIDIS, A.; KONTOPOULOS, N. (Bulletin of the Geological Society of Greece, 2018)
In order to estimate the palaeoflow direction of the submarine fans, deposited in the Internal Ionian subbasin of the Pindos Foreland, fifty-one positions along the sub-basin were selected and measurements of palaeocurrents indicators such as flute and groove marks were taken. In the studied area the main palaeoflow direction of turbidites was axial, from south to north in the southern part, and from north to south in the northern part. A minor westward palaeoflow direction is also present. These palaeoflow directions were influenced mainly by the regional tectonic activity, such as internal thrusting (Gavrovo Thrust) and differential activity of the Pindos Thrust which subdivided Pindos foreland into narrow linear sub-basins.